The effects of four protocols for the treatment of retained placenta on reproduction performance and milk yield in Holstein cows - MELLADO, M.; SOLANO, R.; VELIZ, F. G.; DE SANTIAGO, A.; GAYTAN, L.; GARCIA, J. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
In a first study, 231 cows with retained placenta (RP) were assigned to four groups and their reproductive performance after treatment was studied. Group 1 received 2.0 mg/kg ceftiofur hydrochloride (CH), 10 mg estradiol cypionate (ECP) and 100 IU oxytocin for three consecutive days (CEO-3; n= 63). Group 2 received the same treatment for six consecutive days (CEO-6; n= 48). Group 3 was treated with CH and oxytocin for three consecutive days (CO-3; n= 68). Group 4 was subjected to the previous treatment for six consecutive days (CO-6; n=52). The control group (n= 62) did not present RP. Conception rates (CR) did not differ between treatments with values of 36.5, 25.0, 30.9, 30.8 and 33.9% for CEO-3, CEO-6, CO-3, CO-6 and control group, respectively. Services per pregnancy did not differ between groups (overall 3.6 ± 2.0; mean ± SD). In a second study, changes in milk production associated with RP were examined in cows receiving the CO-3 protocol. Data came from 360 cows with RP and 1623 served as controls. Mean 305-d milk yield was 283 ± 43 kg lower (P<0.05) in cows with RP compared to controls. It was concluded that either prolonged (6-d) or short (3-d) application of CH in combination with oxytocin and ECP were equally effective in preventing a reduction of the reproductive performance in cows suffering RP. Additionally, RP was associated with a 3% decrease in 305-d milk production.